Spectral Enhancement of a SiPM Array-Based Radiation Detector - Harn R. (EDP Sciences, 2021)
Silicon Photomultipliers (SiPMs) have many advantages when used in radiation detectors. Low bias voltage, compactness and immunity to electromagnetic interference are among their prominent benefits. However, due to their small size, usually an array of SiPM components is required in order to cover the coupling surface area of a scintillator. Since the SiPM is a semiconductor, biased in a reversed voltage, gain variation and strong temperature dependence are introduced. As a result, SiPM-based detectors, particularly an array of SiPMs, undergo spectral signal to noise ratio reduction. This work studies the effect of the SiPM breakdown voltage variation on the obtained energy spectrum and proposes an electronic approach to overcome this technological drawback. This developed technology provides an adequate temperature-dependent, commonly distributed high bias voltage and an individual offset-voltage fine tuning that enables adjustment of all the SiPM components to their optimum operating points. Powerwise it is beneficial to operate SiPM at lower voltages, where undesirable gain variation is more dominant. The proposed solution enables working at lower bias voltages, which provides lower power consumption and better radiation hardness, while yielding an enhanced spectrum resolution. The proposed electronic approach enhances the obtained spectra, reducing the noise threshold by 16 % when working at 1 V overvoltage. Hence provides an enhanced signal to noise ratio over the traditional biasing methods.